Extension Agents’ Content Preference and Information Utilization of Agricultural Extension Publications: A Case Study in the State of Pahang, Malaysia - Wok, Saodah (1981)
The study emphasize don the assessment of Agricultural Extension Publications that was made by extension agents in three randomly selected districts namely, Temerloh, Kuantan and Pekan in the state of Pahang. The general objective of the study was to determine the extension agents' content preference in the Agricultural Extension Publications and the extent of utilization of agricultural information by extension agents in the course of carrying out their duties. The concern for the study arose as a result of the realization of the existence of many locally published Agricultural Extension Publication sin the country. Thus, it was envisaged that it was pertinent to make an evaluation of such publications. The study at tempted to find out extension agents' other sources of agricultural information, their information needs, reading habits, their views and opinions regarding the Agricultural Extension Publications that they read and the reasons for reading such publications.